2019
DOI: 10.1109/access.2019.2954744
|View full text |Cite
|
Sign up to set email alerts
|

Skeleton-Based Action Recognition With Key-Segment Descriptor and Temporal Step Matrix Model

Abstract: Human action recognition based on skeleton has played a key role in various computer visionrelated applications, such as smart surveillance, human-computer interaction, and medical rehabilitation. However, due to various viewing angles, diverse body sizes, and occasional noisy data, etc., this remains a challenging task. The existing deep learning-based methods require long time to train the models and may fail to provide an interpretable descriptor to code the temporal-spatial feature of the skeleton sequence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Prior research on skeleton-based action recognition demonstrated the paramount importance of data preprocessing [9], [24], [25], [26], [27], [28], [29]. In the context of this study, the input features are categorized into four distinct groups, namely: 1) position P, 2) velocity V , 3) bone B ∈ {L, β}, and 4) acceleration features A, corresponding to the fundamental kinematic properties of the human body [30].…”
Section: B Data Representationmentioning
confidence: 99%
“…Prior research on skeleton-based action recognition demonstrated the paramount importance of data preprocessing [9], [24], [25], [26], [27], [28], [29]. In the context of this study, the input features are categorized into four distinct groups, namely: 1) position P, 2) velocity V , 3) bone B ∈ {L, β}, and 4) acceleration features A, corresponding to the fundamental kinematic properties of the human body [30].…”
Section: B Data Representationmentioning
confidence: 99%
“…It is a representation easily given by off-the-shelf body pose detectors and potentially allows to perform HAR in real time. Most of the work follows a supervised learning framework where the set of actions should be pre-defined and annotated for training a model [3], [4], [33], [34], [35], [36]. Whereas unsupervised HAR (U-HAR) approaches are in general under-performing compared to their supervised counterparts, but i) they can provide a more robust adaptation to real-world applications as they do not need re-training when the scenario of application changes and ii) they eliminate the need for very expensive and time-consuming annotation efforts.…”
Section: A Unsupervised Skeleton-based Human Action Recognitionmentioning
confidence: 99%
“…For the former, based on empirical knowledge of human body, the relations among joints and limbs under a particular action is calculated with explicit equations [120], [121], [122], [123], [124], [125], [126].…”
Section: Introductionmentioning
confidence: 99%